2005
DOI: 10.1111/j.1538-7836.2005.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrothrombocytopenia in velocardiofacial syndrome

Abstract: crystallographic 3-D structure of the fibrinogen c chain shows that the change occurs in an outer region of the molecule ( Fig. 1), distant from the two calcium-binding sites of the c chain which are located within the amino acid sequence defined by residues 311-336 [4]. Moreover, the mutated amino acid does not lie within the regions involved in D-E contact sites [5]. Taken together, these observations suggest that altered fibrin polymerization of fibrinogen Vicenza might not be associated with a direct effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
3
12
0
2
Order By: Relevance
“…This was contrary to previous case reports where a significant bleeding tendency was not described. 68,69 The blood films in the study demonstrated macrothrombocytopenia, supported by other reports. 68,69 An abnormal PFA-100 result was seen in 71.4% of cases and correlated with bleeding symptoms.…”
Section: Presentation and Diagnosissupporting
confidence: 88%
See 1 more Smart Citation
“…This was contrary to previous case reports where a significant bleeding tendency was not described. 68,69 The blood films in the study demonstrated macrothrombocytopenia, supported by other reports. 68,69 An abnormal PFA-100 result was seen in 71.4% of cases and correlated with bleeding symptoms.…”
Section: Presentation and Diagnosissupporting
confidence: 88%
“…68,69 The blood films in the study demonstrated macrothrombocytopenia, supported by other reports. 68,69 An abnormal PFA-100 result was seen in 71.4% of cases and correlated with bleeding symptoms. Impaired platelet response to ristocetin was reported in 33.3% and impaired responses to TRAP were present in 47.6% of cases.…”
Section: Presentation and Diagnosissupporting
confidence: 88%
“…Asthma Allergy Immunol 2016;14:129-142 22q11.2 delesyonlu hastaların %90'ından fazlasında, delesyonlu kromozom bölgesinde, platelet adezyonu için kritik olan ve agregasyon ve trombin-aracılı aktivasyon için önemli olan platelet GPIb-V-IX reseptörünün bir subünitesini kodlayan GPIb beta geni bulunur (35). Bu genin defekti, GPIb-V-IX'un sayısal veya fonksiyonel defektine neden olur.…”
Section: Hematolojik Bulgularunclassified
“…Bu nedenle BSS'lu hastalardaki kadar olmasa da platelet volümlerinde yükseklik sözkonusudur. Tüm bunlara rağmen, DGS'lu hastalarının kanamaya artmış meyil olduğunu gösteren yayın azdır (35). DiGeorge sendromunu, kalıtsal dev platelet hastalığı sebebi olan 12 hastalıktan birisi kabul eden yayınlar da vardır (36).…”
Section: Hematolojik Bulgularunclassified
“…X-linked thrombocytopenia 52 Familial platelet disorder with predisposition to acute myelogenous leukemia 53 Amegakaryocytic thrombocytopenia 54 Amegakaryocytic thrombocytopenia with radioulnar synostosis 55 Thrombocytopenia with absent radii 56 Bernard-Soulier syndrome 6,57 Velocardiofacial/DiGeorge syndrome 58 VWD type 2B/platelet type VWD 59 Benign Mediterranean macrothrombocytopenia 60 X-linked thrombocytopenia and dyserythropoiesis with or without anemia/X-linked thrombocytopenia-thalassemia 61…”
Section: Was 51mentioning
confidence: 99%